2019
DOI: 10.1080/09540121.2019.1601676
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and treatment adherence among HIV-infected migrants

Abstract: Diagnosing symptoms of psychological distress can be challenging in migrants living with HIV (MLWH) living in Western Europe. We evaluated the Hospital Anxiety and Depression Scale (HADS) as a screening tool for psychological distress. Additionally, the association between psychological distress and adherence to combination Antiretroviral Therapy (cART) was determined. Socio-demographic and clinical characteristics, psychosocial variables, and selfreported adherence to cART data were collected. 306/352 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
1
10
1
Order By: Relevance
“…This was an early attempt to examine how self-stigma and resilience could be associated with psychological distress in the context of a devalued minority group in Hong Kong. We found that 39% of FDH were at risk for high psychological distress (HADS-total Ն15), which was comparable with the estimates among HIV positive migrants in the Netherlands (Been et al, 2019), European parents of children with a chronic illness (Haverman et al, 2013), and Korean cancer survivors (Shim, Shin, Jeon, & Hahm, 2008). Its high prevalence highlights the importance of understanding the correlates of distress for FDH in Hong Kong.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This was an early attempt to examine how self-stigma and resilience could be associated with psychological distress in the context of a devalued minority group in Hong Kong. We found that 39% of FDH were at risk for high psychological distress (HADS-total Ն15), which was comparable with the estimates among HIV positive migrants in the Netherlands (Been et al, 2019), European parents of children with a chronic illness (Haverman et al, 2013), and Korean cancer survivors (Shim, Shin, Jeon, & Hahm, 2008). Its high prevalence highlights the importance of understanding the correlates of distress for FDH in Hong Kong.…”
Section: Discussionsupporting
confidence: 80%
“…A recent review has supported that the HADS-total score is widely used to represent psychological distress in the general public and medical populations (Bjelland, Dahl, Haug, & Neckelmann, 2002). A cut-off point of 15 is suggested as an indicator of having risk for psychological distress (Been et al, 2019; Haverman et al, 2013). The HADS-total score has also been shown to be associated with other commonly used distress measures (e.g., Distress Thermometer; Haverman et al, 2013; The Southern European Psycho-Oncology Study Group et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Migrants in Sweden are often economically more vulnerable than Swedish-born citizens [ 53 ]. Their financial hardship may be indicative of the combination of migration and HIV status, suggesting being a migrant indirectly increases psychological distress [ 49 , 53 , 54 ]. In contrast to Stanley et al’s study [ 14 ], time with diagnosed HIV infection had a strong indirect effect on hopelessness through age.…”
Section: Discussionmentioning
confidence: 99%
“…Prisoners with perceived stigma due to HIV status are more likely to be depressed [108]. One-third of migrants living with HIV report experiencing psychological distress [109]. Screening and treatment for CMHD disorders will be essential in improving HIV care in vulnerable populations.…”
Section: Mental Health In Plwh From Vulnerable Groupsmentioning
confidence: 99%